Do Subjective Effects from Alcohol and Cannabis Predict Simultaneous Use During a Decision-Making Task? - Waddell, Jack T.; Corbin, William R. (Substance Use & Misuse, 2024)
Background: Simultaneous alcohol and cannabis use is associated with negative outcomes, yet little is known about what motivates the decision of simultaneous use. One possibility is that early-episode subjective effects motivate simultaneous use to complement or replace the first substance's effects. The current study used a hypothetical decision-making task to test this hypothesis. Objectives: College students (N = 486) were presented eight scenarios characterized by alcohol/cannabis subjective effects (i.e., high/low arousal positive [e.g., excited, relaxed], high/low arousal negative [e.g., aggressive, dizzy]) and asked their likelihood of simultaneously using the other substance per scenario. Multilevel modeling tested whether subjective effect scenarios predicted a higher likelihood of simultaneous use and whether ordering moderated this association. Results: Task-based simultaneous use likelihood was associated with self-reported simultaneous use, showing task validity. Scenarios characterized by high/low arousal positive effects were associated with higher likelihood of simultaneous use, whereas high/low arousal negative scenarios were associated with lower likelihood. Alcohol vs. cannabis-first scenarios were associated with higher likelihood of simultaneous use, and significant interactions were observed for high/low arousal positive and high arousal negative effects. High arousal positive scenarios were associated with higher likelihood of simultaneous use when cannabis was used first, low arousal positive scenarios with higher likelihood when alcohol was used first, and high arousal negative scenarios with lower likelihood when cannabis was used first. Conclusions: Beginning-of-episode subjective substance effects may be a promising event-level predictor of simultaneous use, and just-in-time interventions may benefit from targeting the ordering and subjective experiences of alcohol and cannabis use.